Assessing the resistance of collard greens genotypes to the cabbage aphid (Brevicoryne brassicae) (Hemiptera: Aphididae) - Canassa, Vinicius Fernandes [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Sacilotto, Matheus Gerage [UNESP]; Lourencao, Andre Luiz; Fanela, Thiago Luis Martins [UNESP] (Springer, 2021)
Severe attacks of Brevicoryne brassicae (Hemiptera: Aphididae) on brassica crops may lead to a significant decrease in yield and can cause plant death. Host plant resistance is considered a valuable tool in integrated pest management and can assist in reducing the damage caused by aphids. This study evaluated the behavioral and biological parameters of B. brassicae in 37 Brassica oleracea (L.) var. acephala genotypes, and aimed to characterize the mechanisms of antixenosis and/or antibiosis. In antixenosis, plants were arranged in a circle inside an arena, releasing to the center one hundred adult aphids. The number of insects was evaluated at 1, 2, 3, 6, and 24 h after infestation. For antibiosis, 30 adults were confined inside each clip-cage on each genotype. The total number of nymphs; number of nymphs per adult per day; total nymphs until 10 d after the first nymph had been produced; duration of the pre-reproductive phase; duration of the reproductive phase; nymphal survival; adult longevity; nymph-adult period and nymphal mortality at 5, 7 and 10 d were evaluated. Several genotypes showed be less infested and more harmful to B. brassicae on collard greens. The genotypes 20T, 24X, 18R, 22V, 15O, 19S, 27VA, and 17Q were the least infested in the antixenosis 24 h free-choice test. 2B, 5E, 8H, 19S, 21U, 27VA, 30OP, PE, MGH, and TP genotypes prevented B. brassicae from completing nymphal period, indicating antibiosis and/or antixenosis expression. 4D, GAU, 20 T, 14 N, and MGI genotypes prevented the aphid from reaching the reproductive phase. These genotypes may be useful for breeding programs that focus on the resistance of collard greens to aphids.
Keywords: Brevicoryne brassicae; Host plant resistance; Brassiaca oleracea var; acephala; Antibiosis; Antixenosis